Open controversies on the treatment of undescended testis: An update - Liu, Jie; Xiu, Wenli; Sui, Bangzhi; Jin, Zhiyuan; Xu, Xudong; Xia, Nan; Duan, Guangqi (Frontiers in Pediatrics, 2022)
Cryptorchidism is a common congenital malformation in pediatric urology. Although there have been many studies on the etiology of the disease, it has not been fully clarified, and while its diagnostic and treatment models have gradually approached standardization and systematization, some controversies regarding treatment remain. Additionally, although ultrasound is a noninvasive examination without ionizing radiation, its role in the evaluation of cryptorchidism remains controversial. The main basis for treating cryptorchidism is orchidopexy, and the main view on treatment age is that treatment should be performed between 6 and 12 months after birth, but no more than 18 months after birth. The view on hormone therapy is still controversial because most scholars believe that early surgery is the key to treatment. There are many surgical treatment methods for cryptorchidism, including traditional open surgery and laparoscopic surgery, which provide satisfactory results. In conclusion, the treatment of undescended testis had been largely standardized, apart from the treatment of high intra-abdominal testis, which remains a matter of debate.